2022
DOI: 10.1177/07067437221128462
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Current PTSD Symptoms Among a Sample of Black Individuals Aged 15 to 40 in Canada: The Major Role of Everyday Racial Discrimination, Racial Microaggresions, and Internalized Racism

Abstract: Objective Most Black individuals in Canada report having experienced racial discrimination. Although previous studies have shown that there is a strong relationship between racial discrimination and posttraumatic stress disorder (PTSD), no studies in Canada have documented this association among Black individuals. The present study documents (1) the prevalence of PTSD among Black individuals using data from the Black Communities Mental Health project and (2) risk factors associated with PTSD, including racial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…We used the item of the major experiences of discrimination scale evaluating racial discrimination in healthcare settings: “ Have you been unfairly treated in a hospital or other health services? .” 23 The scale has been used in recent studies among Black and racialized communities in Canada and have shown a good internal consistency 19,24 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the item of the major experiences of discrimination scale evaluating racial discrimination in healthcare settings: “ Have you been unfairly treated in a hospital or other health services? .” 23 The scale has been used in recent studies among Black and racialized communities in Canada and have shown a good internal consistency 19,24 …”
Section: Methodsmentioning
confidence: 99%
“…23 The scale has been used in recent studies among Black and racialized communities in Canada and have shown a good internal consistency. 19,24…”
Section: Major Racial Discrimination In Healthcare Servicementioning
confidence: 99%
“…A previous epidemiological study by Van Ameringen et al (2008) suggested that almost one in 10 Canadians have experienced PTSD at some time in their lives but this estimate, in all likelihood, substantially underestimates the breadth of the problem for various reasons, especially among people with unique stressors. It does not reflect the exceptionally high prevalence found among Black people, for instance (see Cénat et al, 2023) and changing diagnostic criteria point to the urgent need for a new national study. We know that PTSD is found far too often among members of the military and police, as well as first responders but PTSD is detectable in people in Canada from many different backgrounds (see Marrello et al, 2021; Weeks et al, 2021).…”
Section: Why Engage In Sharing Knowledge and Advice?mentioning
confidence: 99%
“…Additionally, the minority stress faced by Black individuals in Western societies may contribute to worsening substance use when facing racial discrimination (Pittman, Brooks, et al, 2017; Pittman, Kim, et al, 2017). The CoRT asserts that the recurrent, repetitive, constant, inevitable, and cumulative nature of racial discrimination—which Black, Indigenous, and people of color (BIPOC) experience in Western societies—exposes them to significant lifelong consequences, including mental health issues and risky behaviors such as alcohol and substance use (Cénat, 2022a; Cénat, Dalexis, et al, 2022).…”
Section: The Present Studymentioning
confidence: 99%